Instrumental Activities of Daily Living in Pediatric Occupational Therapy Practice: A Survey of Current Practice Patterns and Perceived Importance. (1st December 2021) - Shin, Julia; Decker, Bonnie; Blanchard, Shirley
Abstract: Aims: We investigated how instrumental activities of daily living (IADLs) are addressed and perceived, in comparison to activities of daily living (ADLs), across preschool (3–5 years), middle childhood (6–11 years), early adolescence (12–15 years), and older adolescence (16–21 years) age groups by pediatric occupational therapy (OT) practitioners. Method: 247 OT practitioners with at least 2 years of pediatric work experience in the U.S. completed an electronic survey assessing (a) type of IADLs most frequently addressed and (b) type of IADLs perceived as most important across the age groups. Results: With increasing age of children and adolescents with disabilities, frequency and perceived importance of addressing IADLs increased in comparison to ADLs; there was a statistically significant relationship between the frequency and the perceived importance of addressing IADLs for all 12 activities across the age groups. Conclusion: The decision-making process in addressing IADLs in pediatric OT practice was significantly influenced by the practitioners' perceived importance of IADLs.